A parochial lost cause? The micro-politics of language revitalization initiatives in Jersey (Channel Islands). Issue 1 (June 2016) - Hopkins, Mark
Abstract : The patois still understood, written and occasionally spoken in the island of Jersey has both an illustrious history as the linguistic signifier of this "piece of France thrown into the sea and picked up by England" (Hugo 1866), and a twenty-first-century relevance as a case study for sociolinguistic obsolescence, even irrelevance. This paper aims to investigate its status, form and expression in popular literature. The method employed is principally documentary analysis, in an attempt to situate jèrriais in the current debate about endangered languages and the effects on a minority (insular) language of its contact with two competing high-status world languages, although personal experience of living on the island in the 1980s is also drawn upon. In the author's view, the crucial factor in the obsolescence of jèrriais is the widely held belief – even among scholars, see Jones (2001) – in its normative difference from 'proper' French and an unquestioning acceptance by Jersey residents of their own position in the Anglophone world. Historically speaking, it is the centuries (since 1204) of political isolation from the French-speaking Normandy peninsula that has in his view led to the terminal decline of jèrriais.